Violating Food System Workers' Rights in the Time of COVID-19: The Quest for State Accountability. (1st April 2021) - Elver, Hilal; Shapiro, Melissa
Abstract : Food system workers, accounting for nearly one-third of the global workforce, are vital to the universal realization of the right to food, yet face formidable barriers to the realization of their own rights. Despite state obligations to protect, respect, and fulfil the rights of workers under international human rights law, gaps in legal frameworks and lack of political will have left food system workers exposed to discrimination and abuse at the hands of private actors. Migrant workers, as well as racial and ethnic minorities, in particular, face targeted exploitation without redress. Case studies demonstrate the extent of this harm, even as governments designate workers as "essential" during the COVID-19 pandemic. The authors of this article argue that deliberate inaction by states to extend meaningful protections to workers or indict exploitative actors demonstrates the need for a new state crime—one that holds accountable governments that are complicit in the grave violations of workers' fundamental rights.